(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This study offers a comprehensive linguistic examination of national cultural stereotypes associated with the English-speaking world. By analyzing linguistic structures, discourse strategies, and culturally marked expressions in English, this article explores how stereotypes function as communicative tools reflecting collective identity. It also discusses their implications in cross-cultural interaction, language teaching, and global media.